Optimalisasi Standar Operasional Prosedur (SOP) Pencairan Anggaran Secara Digital pada Deputi Bidang Keuangan BPJS Ketenagakerjaan - Nisrina Thufailah; Mohammad Benny Alexandri (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
BPJS Employment requires budget planning to support its smooth operations. So that the budget can be realized properly, it is contained in the Regulation of the Directors of BPJS Employment Number 35/PERDIR.07/12/2022 which regulates the Procedures and Authority for Budget Disbursement. Even though these procedures have been implemented, there are still problems in the budget disbursement process. This research aims to find out how BPJS Employment applies digital budget disbursement SOP optimization to the Deputy for Finance. This research uses a qualitative method with a descriptive approach, which was carried out through interviews, observation and documentation to identify the optimization steps needed. The main finding of this study is the optimization of digital budget disbursement SOPs which have been implemented by the Deputy for Finance at BPJS Employment.  This causes problems, such as irregular return of documents, especially due to lack of clarity in the regulations regarding budget disbursement deadlines. Apart from that, changes have been proposed in optimizing procedures, such as implementing a maximum time limit for returning files of two working days, providing a maximum approval time limit of five working days for the cashier section, and limiting the number of daily disbursement applications, as well as creating a monitoring dashboard to increase transparency and effectiveness in budget management.